Cytostatic-drugs handling in hospitals: Impact of contamination at occupational environments - Silva, João (2018)
The manipulation and administration of cytostatics is performed in hospital pharmacies and day hospitals respectively. In each of these sites, the preparation or administration process occurs at different workplaces. In these places spills can occur, which in themselves, cause contamination in the workplace. Of these, the laminar flow hood and the patient’s chair are the places where the greatest number of spills occurred. Through the chi-square test of cross-tabulation, an analysis was made to verify if there is a relation of independence or dependence between the different workplaces and work routines. Results show that there is a significant association between the trays, the laminar flow hood, the administration cart and the patient’s chair, with the intervals scheduled between the preparation/administration periods.